2006
DOI: 10.1152/japplphysiol.00497.2006
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training increases basal limb blood flow and vascular conductance in aging humans

Abstract: Age-related reductions in basal limb blood flow and vascular conductance are associated with the metabolic syndrome, functional impairments, and osteoporosis. We tested the hypothesis that a strength training program would increase basal femoral blood flow in aging adults. Twenty-six sedentary but healthy middle-aged and older subjects were randomly assigned to either a whole body strength training intervention group (52 +/- 2 yr, 3 men, 10 women) who underwent three supervised resistance training sessions per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
1
22

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 28 publications
10
65
1
22
Order By: Relevance
“…Recent studies reported that resistance training or aerobic training increased brachial and femoral artery diameter. 31,[34][35][36] These results suggest that both types of training cause enlargement at the level of the major conduit arteries. The present findings extend these results from endurance-trained individuals to those who perform resistance training.…”
Section: Muscle Contraction Timing and Vascular Function T Okamoto Et Almentioning
confidence: 73%
See 1 more Smart Citation
“…Recent studies reported that resistance training or aerobic training increased brachial and femoral artery diameter. 31,[34][35][36] These results suggest that both types of training cause enlargement at the level of the major conduit arteries. The present findings extend these results from endurance-trained individuals to those who perform resistance training.…”
Section: Muscle Contraction Timing and Vascular Function T Okamoto Et Almentioning
confidence: 73%
“…Short-term resistance training increases basal femoral BF and VC, which suggests that resistance training affects basal limb perfusion through a mechanism related to its effects on glucose uptake. 35 Therefore, hemodynamic improvement induced by resistance training is clinically important. However, the physiological mechanisms underlying the changed hemodynamics during resistance training remain obscure.…”
Section: Muscle Contraction Timing and Vascular Function T Okamoto Et Almentioning
confidence: 99%
“…Based on means, SD , and anticipated effect sizes from previous studies, sample sizes were determined for group differences in glucose responses to dietary (primarily dairy) interventions (Gannon, Nuttall, Lane, & Burmeister, 1992; Liljeberg Elmstahl & Bjorck, 2001; Nilsson, Stenberg, Frid, Holst, & Bjorck, 2004; Ostman et al., 2001; von Post‐Skagegard et al., 2006). The power calculation for femoral blood flow and vascular conductance was performed on our previous published work because there are no published group data for these variables (Anton et al., 2006b; Dinenno, Tanaka, Stauffer, & Seals, 2001; Dinenno et al., 2001). The magnitude of group differences ranged from 15% (arterial blood pressure) to 45% (femoral vascular resistance), representing physiologically meaningful differences.…”
Section: Methodsmentioning
confidence: 99%
“…Foram encontradas 12 referências sobre o treinamento com pesos em longo prazo e a PA de repouso em normotensos (7,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) e seis referências em hipertensos (5,32,(40)(41)(42)(43) . Dos estudos com normotensos, duas referências possuíam dois grupos experimentais (35,37) .…”
Section: Treinamento Com Pesos E Pressão Arterial De Repousounclassified